Cytogenetic analysis of species of the genera Acestrorhynchus, Oligosarcus and Rhaphiodon (Teleostei: Characiformes) - Martinez, Emanuel Ricardo Monteiro [UNESP]; Oliveira, Claudio [UNESP]; Júlio-Junior, Horácio F. (Firenze University Press, 2004)
In the present study the karyotypes and the number and position of nucleolus organizer regions (NORs) of four species of Characiformes are described. The analyses showed that Acestrorhynchus lacustris had 2n=50 chromosomes (8M+34SM+6ST+2A), Oligosarcus longirostris had 2n=50 chromosomes (2M+20SM+10ST+18A), Oligosarcus cf. paranensis from Keller and Mourão rivers had 2n=50 chromosomes (2M+26SM+8ST+14A), and Rhaphiodon vulpinus had 2n=54 chromosomes (32M+12SM+8ST+2A). The number of NOR-bearing chromosome pairs ranged from one to three among the species studied. The results available show that there is no variation in the diploid number within the genera analyzed. However, clear differences related to the karyotypic formulae and the number and position of Ag-NORs were found even in the comparison between populations. The possible relationships between the genera analyzed and other Characiformes are discussed.
Keywords: Ag-NOR; Chromosomes; Evolution; Fish; Karyotype; Acestrorhynchus; Acestrorhynchus lacustris; Characiformes; Oligosarcus; Rhaphiodon; Rhaphiodon vulpinus; Teleostei